MARKETING IN THE SOCIO-ECONOMIC DEVELOPMENT OF UKRAINIAN CITIES IN THE CONTEXT OF EUROPEAN DIMENSION - Volodymyr Pylypchuk; Arutiun Papoian (Izdevnieciba "Baltija Publishing", 2019)
The article analyses the main aspects of the philosophy, methodology and tool of marketing in socio-economic development of cities in Ukraine. The attention is focused on perceived deficiencies in the study area. Reviewed basic information on the implementation of marketing principles in the development of cities of Ukraine. Revealed questions the need to define, first of all, the development strategy of the city, and then the formation of the marketing strategy and its implementation. The study highlighted the complexity of the concept of development of the city, which is not limited only to the growth of economic potential. The conclusion about necessity of use of experience of European countries in the use of marketing in the formation of the concept of development of cities of Ukraine. Focused attention on the fact that the leading role in shaping the development of cities, the use of local resources and enhancement of endogenous potential of the city is given primarily to local authorities. It is found that for the application of marketing in the time of the development of cities in Ukraine need professional and highly qualified team that will deal with these issues. Also drawn attention to the fact that Ukraine, unfortunately, cannot boast of a system of scientific researches in the field of marketing of the city. And their effective implementation. Local authorities in this sphere are chaotic because they have no clear understanding of a systematic approach to the planning and development of the city. The experience of leading European countries in the use of marketing methodologies and techniques in the elaboration of development plans of cities. It is found that the governments of many countries have used marketing tools in the implementation of programmes to combat alcoholism, Smoking and drug abuse, energy conservation, compliance with traffic rules, the decision of problems of the uneven distribution of productive forces, the regulation of the tourism industry, the use of marketing to enhance socio-economic development, improving the competitiveness of the region and implementation of investment planning, etc. The necessity of applying the European experience of marketing in the formulation of plans for development of cities and regions of Ukraine, as well as the development and implementation of a comprehensive system of measures by local authorities in partnership with other stakeholders, which should consist in: developing a development strategy; identification of local advantages and unique territorial features; developing effective marketing strategies; development of local infrastructure; dissemination of educational programs; creation of organizational structures for marketing; forming partnerships; creation of an effective network of information and communication sphere, etc. In general, it is concluded that marketing in local self-government helps to understand the economic and social interests of citizens, because the realization of these interests is the ultimate goal of the activity of all authorities and the state as a whole, and contributes to the formation and development of cities not only in Ukraine, but also in all over the world.